Enhancing health facility-based data quality and use for decision making at primary health care units to improve health service delivery of maternal newborn child and adolescent health, Tigray Ethiopia 2018 - Gebreslassie, Assefa Ayalew; Below, Molla Teferi; Ashebir, Mengistu Mitiku; Gezae, Kebede Embaye; Chekole, Mebrahtu Kalayu (Archives of Community Medicine and Public Health, 2020)
Objective: Information use is fundamental for evidence based decision making but data quality and information use in health facility is limited in low and middle income countries. Therefore, a facility based cross sectional using mixed approach was conducted to assess data quality and use for decision making in 12 selected health facilities of Tigray, Ethiopia, 2018. Results: District Health Information System 2 (DHIS2) software was practiced in 12 of the facilities. Completeness and consistency rate of register and reports was 53.5%, 56.3%, and 38.9%. Respectively. The lot of quality assurance system of service and disease report was 7(61.1%). The performance monitoring team is established decision-making rate on key coverage indicators was 42.9%. Comparisons of performance in a district /national targets were 5(41.5a high rate of incompleteness, inconsistencies, low lots of data assurance and low use of data for decision making. Therefore, DHIS2 tool needs to be used to generate a report, use data and disseminating platforms both inside and outside health facilities using the website and other channels.